The value of cardiac magnetic resonance and distribution of late gadolinium enhancement for risk stratification of sudden cardiac death in patients with hypertrophic cardiomyopathy. Issue 1 (July 2016) - Klopotowski, Mariusz; Kukula, Krzysztof; Malek, Lukasz A.; Spiewak, Mateusz; Polanska-Skrzypczyk, Magdalena; Jamiolkowski, Jacek; Dabrowski, Maciej; Baranowski, Rafal; Klisiewicz, Anna; Kusmierczyk, Mariusz; Jasinska, Anna; Jarmus, Ewelina; et al.
Abstract: Background: The presence of late gadolinium enhancement (LGE) in hypertrophic cardiomyopathy (HCM) is associated with worse clinical outcome and the extent of LGE predicts the increased risk of sudden cardiac death (SCD). Limited data exist regarding the distribution of LGE. We attempted to verify whether the presence of LGE outside the interventricular insertion points carries additional risk for patients with HCM. Methods: In this prospective study, 328 patients with HCM, who underwent cardiac magnetic resonance (CMR) were enrolled. Five major risk factors for SCD were assessed in all patients. The median follow-up was 37 months. Results: LGE was detected in 226 (68.9%) patients. In 70 (21.3%) patients it was present only at the interventricular insertion points – LGE (+) group, while in 156 (47.6%) it was noted in other locations – LGE (++) group. Primary endpoint defined as SCD or appropriate implantable cardioverter-defibrillator intervention occurred in 14 (4.3%) patients, one in LGE (+) and 13 in LGE (++). In multivariable analysis including five traditional risk factors and left ventricular ejection fraction <50%, only the presence of LGE outside the insertion points was a significant predictor of SCD/aborted SCD (HR 10.01, 95% CI 1.21–83.86, p = 0.033). The performance of the multivariable sudden cardiac death risk model was improved by the addition of LGE (++) to the traditional risk factors (likelihood ratio p = 0.005). The Kaplan–Meier curves showed better event-free survival in the LGE (−) and LGE (+) patient groups compared to the LGE (++) group. Conclusions: In HCM patients, presence of LGE outside interventricular insertion points is associated with increased risk of sudden cardiac death or its equivalent as well as overall mortality. Cardiac fibrosis as a substrate for SCD in HCM may be identified on CMR and serve as an imaging biomarker of increased risk.